Effect of sago starch paste ingestion during steady-state cycling on subsequent time-real performance - Chen Chee, Keong (Pusat Pengajian Sains Perubatan, 2012)
This study was undertaken to determine the effects of ingesting a specific form of a sago starch preparation before and during prolonged steady state cycling exercise in the heat on subsequent time-trial performance. Fifteen, heat acclimatised recreational cyclists completed two separate, randomised trials of 90 minutes cycling at 60% of VOzmax. followed by a 15-min performance ride in a temperature and humidity controlled chamber maintained at - 31°C and a relative humidity of -70%. Pre-exercise feedings consisted of sago starch paste (SBEx) amounting to 0.75g carbohydrate (CHO/kg body weight or a similarly flavoured, coloured and textured placebo (PBEx). During the steady state ride, subjects either consumed liquid sago starch paste supplying 15g CHO (SDEx) or a placebo (PBDex) at 20-minute intervals. To promote thermoregulation, subjects were fan cooled throughout both exercise periods. Core body temperatures were measured and recorded at 10-minute intervals during the steady-state ride and on completion of the performance ride. The amount of work produced in kilojoules (kJ) during the performance ride was taken as a measure of performance. Results indicated that the SBExSDEx trial produced significantly higher mean work output during the performance ride (146.9±21.5kJ or 33.2% improvement, p<0.001) compared to the PBExPDEx trial (110.3±26.2 kJ). Core body temperatures prior to exercise were similar for both trials (p=0.45) but at completion of the steady state ride, it was significantly higher during the PBExPDEx trial (38.4±0.4°C) compared to the SBExSDEx trial (38.1°C,p=0.001). Similarly, core body temperature at the end of the time-trial was significantly higher during the PBExPDEx trial (38.5±0.4°C) compare to SBExSDEx trial (38.3±0.3°C),p=0.017). This present study indicated that sago starch paste feedings before and during prolonged sub-maximal exercise can improve time-trial performance while at the same time attenuating the rise in core body temperature.